Molecular identification and life cycle of Black Soldier fly (Hermetia illucens) in laboratory - Ferdousi, Lailatul; Sultana, Nahid; Helal, MA Al; Momtaz, Nasima (Bangladesh Journal of Zoology, 2021)
Molecular identification and life cycle of the Black Soldier Fly (BSF), Hermetia illucens were carried out from the Bangladesh bio-geographical area. The sequencing result and phylogenetic analysis of BSF showed 99-100% similarity with H. illucens from GenBank. The average duration of life cycle of male and female were 45.08±4.46d and 46.15± 4.12d respectively. The adult female is 16.3±0.91mm long, whereas the adult male is 14.30±0.19 mm long and smaller than female. The number of eggs per clutch was 537.37±40.21 which hatched in 4.36±0.24 days. The mean duration of the developmental stages were 16.07±2.59, 15.4±2.50, 9.95±1.48 and 10.33±1.89 d for larva, pupa, male and female respectively, when cultured at 29.40±1.77° C, RH 68.25±2.32 %, 14:10 (L: D) photoperiod. The mature larval weight (0.20±0.03 g) was highest among other developmental stages. Bangladesh J. Zool. 48(2): 429-440, 2020